Effect of silver diammine fluoride on micro-ecology of plaque from extensive caries of deciduous teeth - in vitro study - Bao ying Liu; Jin Liu; Di Zhang; Zhi lei Yang; Ya ping Feng; Meng Wang (BMC, 2020)
Abstract Background The mechanism of action of silver diammine fluoride (SDF) on plaque micro-ecology is seldom studied. This study investigated micro-ecological changes in dental plaque on extensive caries of deciduous teeth after topical SDF treatment. Methods Deciduous teeth with extensive caries freshly removed from school children were collected in clinic. Unstimulated saliva collection and initial plaque sampling were done before tooth extraction, then each caries was topically treated with 38% SDF in vitro. After intervention, each tooth was stored respectively in artificial saliva at 37 °C. Repeated plaque collections were done at 24 h and 1 week post-intervention. Post-intervention micro-ecological changes including microbial diversity, microbial metabolism function as well as species correlations were analyzed and compared after pyrosequencing of the DNA from the plaque sample using Illumina MiSeq platform. Results After SDF application, microbial diversity decreased (P > 0.05), although not statistically significant. Microbial community composition post-intervention was noticeably different from that of supragingival and pre-intervention plaque as well as saliva. At 1 week post-intervention, the relative content of Pseudomonas, Fusobacterium and Pseudoramibacter were higher than before, while most of the other bacteria were reduced, although the changes were not statistically significant (P > 0.05). The inter-microbial associations became more complex, much more positive associations among survived bacteria were observed than negative ones. COG function classification diagram showed carbohydrate transportation and metabolic functions in the plaque were significantly reduced at 24 h and 1 week post-intervention. Conclusions SDF has extensive antimicrobial effect on dental plaque, which may reduce carbohydrate metabolism in dental plaque and help promote new balance of the plaque flora.